Resistance to Ibritumomab in Lymphoma (Resistance to Targeted Anti-Cancer Therapeutics, 2018)
This volume, in discussing resistance to ibritumomab, will focus on the mechanism, hematological aspects, radiological and nuclear medicine aspects, and medical physics that deal with radiation dosimetry, and will outline future prospects for overcoming resistance and enhancing efficacy of ibritumomab.